Lexical stock under scrutiny: exploring the mental representations of morphologically complex structures - Pakuła, Łukasz Piotr (My University, 2014)
The following paper is devoted to the exploration of morphological relations between mental representations of words and their textual realisations. The ability to read written texts has accompanied humans for about six thousand years as opposed to the spoken language which is said to be the more natural mean of communication with a history of about six million years. Both ways of communication have appreciated a long standing tradition, however psycholinguistic research delving into the former phenomenon seems not to have been sufficient to uncover most of its peculiarities. This paper deals with the phenomenon of visual word recognition yet by no means is it thought to exhaust the subject. It has been divided into the following three parts. The first chapter deals mainly with the theoretical approaches to the way humans are able to recognise written texts. Various plausible processes operating at the level of meaning retrieval from the written text are presented. Moreover, factors determining the speed and quality of word recognition are briefly expanded upon. The subsequent part of the present work attempts to provide a concise account of the dominating models of visual word recognition both those which incorporate the role of morphology and those which do not. Additionally, the evolution together with the most recent formulation of the idea of the mental lexicon is explicated. The ultimate part of the paper concentrates on the empirical study which was carried out for the purpose of this thesis. It was modelled on (Pilon 1998) and aimed at verifying the pseudoprefixation hypothesis. The benefit of having a model experiment is that the results of the two studies can be contrasted thus lifting the veil of secrecy on the role of morphology in visual word recognition. The assumption put forward is that if the phenomenon of pseudoprefixation exists the role of morphology in visual word recognition should be acknowledged.
Keywords: psycholinguistics; word recognition; morphology; mental lexicon